Metamaterials: High‐Quality‐Factor Mid‐Infrared Toroidal Excitation in Folded 3D Metamaterials (Adv. Mater. 17/2017). Issue 17 (May 2017) - Liu, Zhe; Du, Shuo; Cui, Ajuan; Li, Zhancheng; Fan, Yuancheng; Chen, Shuqi; Li, Wuxia; Li, Junjie; Gu, Changzhi
Abstract : A 3D toroidal metamaterial is demonstrated in article number1606298 by Junjie Li, Changzhi Gu, and co‐workers, to address the excitation of high‐quality‐factor toroidal moment in mid‐infrared region. The metamaterial composed of metal patterns of well controlled split direction and spatial orientation was fabricated by an ion beam‐induced folding technique on suspended SiN x film. The radiation power of the toroidal dipole in the far‐field can be predominant compared to other dipoles by tuning the incident angle.